Transforming Teaching Practices: The Impact of Leaders Coaching in Educational Settings - Asbari, Masduki (International Journal of Social and Management Studies, 2024)
The study aimed to investigate the impact of leaders coaching on teachers' performance and psychological capital, as well as to explore the mediating role of psychological capital in this relationship. Conducted in seven private junior high schools in Tangerang, the research utilized a simple random sampling method with a sample size of 59 teachers. The findings of the study revealed significant positive effects of leaders coaching on both teachers' performance and psychological capital. This suggests that when school leaders engage in coaching behaviors, it can lead to improvements in teacher performance and the development of psychological resources such as self-efficacy, hope, optimism, and resilience among teachers. Moreover, the study identified that the relationship between leaders coaching and teacher performance was significantly mediated by psychological capital. This implies that the influence of coaching on teacher performance is partially explained by the enhancement of psychological capital. By improving teachers' psychological resources through coaching, school leaders can indirectly contribute to enhancing teacher performance. Overall, the results of this study indicate that leaders coaching plays a crucial role in shaping teachers' performance and psychological well-being. By recognizing the mediating effect of psychological capital, the study suggests that investing in coaching initiatives can not only directly impact teacher performance but also indirectly influence performance through the development of psychological resources. This research contributes to preparing teachers to face the challenges of the education setting by enhancing their readiness and capabilities through effective coaching practices.